Pengembangan Media Pembelajaran Pop-Up Book Pada Mata Pelajaran IPA untuk Meningkatkan Hasil Belajar Siswa SMP Negeri 2 Tompaso - Lumintang, Keren Prily; Rungkat, Jovialine Albertine; Suriani, Ni Wayan (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
This research aims to (1) develop pop-up book learning media in science subjects that are feasible to use; and (2) determine the improvement of student learning outcomes after using pop-up book learning media. The type of research we use is research and development using the ADDIE model. The data collection techniques we used were questionnaires and tests. The research instruments we used were questionnaires and learning outcomes tests. Quantitative and qualitative data analysis techniques were used in this study. The results showed that the validation of subject matter experts was 98%, and learning media experts were 92%. In addition, this pop-up book learning media can also improve student learning outcomes so it is quite effective to use. This can be seen from the N-gain score of 0.62 and the percentage of the N-gain score of 62.18%. Based on these findings, pop-up book learning media in science subjects are feasible to use and can improve student learning outcomes.